EDITORIAL: PUBLIC CONCERNS REGARDING EFFICACY AND SAFETY OF MEDICINES (The East and Central African Journal of Pharmaceutical Sciences, 2018)
A recent debate in one African country regarding cough medicines brought into the fore a simmering public concern regarding efficacy and safety of medicines. The debate was prompted by a retrospective study conducted at Pennsylvania State University which indicated that cough mixtures for children are relatively ineffective and possibly harmful. This information was widely disseminated by a consumer pressure group and published in Consumer Reports. There was an attempt, albeit inadvertently, to distort information which has been in the public domain for several years. Use of cough mixtures generally and specifically in children below six years of age is controversial and there is no consensus among health professionals. This is partly attributed to lack of suitable laboratory models to study cough, which is a symptom rather than a disease. It is, however, generally accepted that use of cough suppressants containing dextromethorphan, codeine and pholcodine is undesirable in this age group. There is extensive published information on this subject, particularly on the internet.
Keywords: PUBLIC CONCERNS REGARDING EFFICACY AND SAFETY OF MEDICINES